Paradigms, Distance Learning, Education and Philosophy - Andrew Higgins (Flexible Learning Association of New Zealand, 2020)
The purpose of this article is to illuminate some of the difficulties experienced by distance educators in the philosophical sense. It will show  distance learning practice is still a highly pragmatic enterprise that is academically successful. Despite its academic success distance learning is not accepted by the education profession generally because it challenges the most fundamental paradigm of western education, namely, the co-location in time and space of teachers, students and resources.  Distance learning challenges the need for a place or institution for study, for example, a school. This appears to disrupt the social and economic imperatives of having a place to work. Finally, distance learning challenges the socialisation purposes used by society through schools to enculture young people.